Causal linkage of subjects to promote science academic performance for the skills-gap - Mayanja, David Dan (African Journal of Education and Practice, 2016)
Purpose: A critical question addressed in this paper concernsthe casual linkage of Ordinary-Level subjects to promote science academic performance. We develop a structural equation model to determine the contribution of vocational, social science and language subjects to students' grades in mathematics and subsequently science subjects. Methodology: The paper uses secondary data from the Uganda National Examinations Board (UNEB) for the year 2014. Findings: The results of structural equation modeling demonstrate that grades obtained in social science and vocational subjects negatively contribute to the grades obtained in mathematics and this effect was significant at 1 and 5 percent level respectively. In contrast, thepath for the latent variable Language show that high academic achievement in Language subjects is positively and significantly (p<.01) related with performance in mathematics. It was also established that grades obtained in mathematics positively significantly (p<.01) impact on the grades obtained in Science related subjects. Policy Recommendation: We recommend that students wishing to specialize in science related disciplines must be informed about the core subjects that enhance their likelihood of understanding science. Going by the findings, teachers should always emphasize the importance of language in developing students' competency in mathematics which also significantly impacts academic achievement in science.